On three symbiotic species of the alpheid shrimp genus Salmoneus Holthuis, 1955 from the Indo-West Pacific, including one new to science (Malacostraca: Decapoda: Caridea) - Anker, Arthur (Zootaxa, 2019)
Three species of the alpheid shrimp genus Salmoneus Holthuis, 1955 associated with burrows of other decapod crustaceans are reported from various Indo-West Pacific localities. Salmoneus venustus sp. nov. is described based on material collected at two distant localities, Nha Trang Bay, southern Vietnam, the type locality of the new species, and the Yiti-Sifah region east of Muscat, northern Oman. Both specimens were collected with the aid of a suction pump applied to burrow entrances or mounds in muddy sand; the holotype was possibly associated with burrows of the callianassid ghost shrimp, Glypturus sp. Salmoneus venustus sp. nov. shares many characteristics with S. latirostris (Coutière, 1897), including the red banding of the pleon, but can be distinguished from S. latirostris and all other species of the genus by a unique combination of morphological characters. The large-sized Salmoneus brucei Komai, 2009 is reported from Sumba, central Indonesia, representing a significant southward extension of the species’ previously known distribution range and the first record since its original description. The callianassid ghost shrimp Lepidophthalmus cf. rosae (Nobili, 1904) is recorded as a new host of S. brucei. Finally, Salmoneus colinorum De Grave, 2004, associated with burrows of larger snapping shrimps from the Alpheus malabaricus Fabricius, 1798 species complex, is reported for the first time from Madang, Papua New Guinea, representing an eastward extension of the species’ previously known distribution range.